INVENTAIRE DES TAXONS POLLINIQUES DES MIELS DE LA ZONE GUINEENNE DU TOGO : CAS DES ZONES ECOFLORISTIQUES IV ET V - Comlan Mawussi Koudegnan; Thérèse M. Edorh; Atsu K. Guelly; Komlan Batawilla; Koffi Akpagana (European Scientific Journal, ESJ, 2012)
Pollen analysis was carried out on samples of natural honey from apiaries located in the following regions: Danyi-Elavanyo, Danyi-Akayo, Igbélékoutsè-Béna and Azianfokopé-Takpla of ecological zones IV and V of the Guinean zone of Togo, where floristic surveys were conducted within a radius of 600 m around each apiary. This analysis of pollen taxa inventory 82 then 43 are identified to specie. This present work has increased the list of honey plants already known 28 new species example. Then, the richness of the flora honey of Togo passes from 79 to 107 species, or about 0,82 % of the flora Togo. The Leguminosae are richer in pollen taxa (i.e. 23,17 % of the all taxa identified). Overall, the “Arboreal Pollen” are represented as “Non Arboreal Pollen”, respectively 87 % against 23 %.